Job quality and turnover intention among ICT employees in Malaysia: employees’ affective commitment as mediator and age as moderator - Hassan, Arif; Juhdi, Nurita; Mustaffa, Nur Fariza (Asian Academy of Management, Universiti Sains Malaysia, 2017)
The paper is based on the concern that rate of turnover of Information and communication technology (ICT) employees in Malaysia is alarmingly high. The study examined the role of job quality as the determinant of turnover. It also examined the relationship between job quality and affective commitment and how this factor-mediated the relationship between job quality and turnover intention. The study also examined the role of employees age as the moderator between job quality and turnover intention. The sample consisted of 243 ICT employees drawn from a mix of industry. The data were collected with the help of standardized instruments. Results were generally in the expected direction. Among the job quality factors appreciation and advancement, teamwork and empowerment, and work conditions were significantly associated with affective commitment. Appreciation and advancement negatively contributed to turnover intention. Additionally, affective commitment negatively but partially mediated the relationship between appreciation and advancement aspect of the job quality with turnover intention. Age showed a full negative moderation effect in the relationship between appreciation and advancement and turnover intention.